2013
DOI: 10.1016/j.jsb.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models of collagen biomineralization

Abstract: Over the last several years, significant progress has been made toward understanding the mechanisms involved in the mineralization of hard collagenous tissues, such as bone and dentin. Particularly notable are the identification of transient mineral phases that are precursors to carbonated hydroxyapatite, the identification and characterization of non-collagenous proteins that are involved in controlling mineralization, and significant improvements in our understanding of the structure of collagen. These advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
202
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(217 citation statements)
references
References 109 publications
5
202
0
10
Order By: Relevance
“…19 Furthermore, mineral exists both within and external to the collagen fibrils (interfibrillar deposition); however, it is generally accepted that the majority of the mineral exists within the fibrils. 30 Interfibrillar mineralization of collagen is directed by the collagen matrix, 31 which leads to nanostructured architecture consisting of uniaxially orientated nanocrystals of HA embedded within and roughly aligned parallel to the long collagen fibril axis. Previous studies have suggested that type I collagen polypeptide stereochemistry and other factors are fundamental in the initial events of mineral deposition with the intrafibrillar spaces of the molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, mineral exists both within and external to the collagen fibrils (interfibrillar deposition); however, it is generally accepted that the majority of the mineral exists within the fibrils. 30 Interfibrillar mineralization of collagen is directed by the collagen matrix, 31 which leads to nanostructured architecture consisting of uniaxially orientated nanocrystals of HA embedded within and roughly aligned parallel to the long collagen fibril axis. Previous studies have suggested that type I collagen polypeptide stereochemistry and other factors are fundamental in the initial events of mineral deposition with the intrafibrillar spaces of the molecule.…”
mentioning
confidence: 99%
“…Tissue localization can give clues to a role but does not provide any functional information. 30 How Ca and PO 4 ions are delivered to the mineralization front is still a matter of debate. Pioneering studies have suggested the role of mitochondria in taking in large amounts of Ca and PO 4 ions, accumulating them, and delivering calcium phosphate in membrane bound vesicles to the extracellular spaces of mineralizing cartilage and bone.…”
mentioning
confidence: 99%
“…17,45 Based on the size exclusion mechanism of intrafibrillar mineralization, 46 PAH is excluded from entering the intrafibrillar compartments of the collagen fibril; depletion of the nucleation inhibitor would result in the formation of crystalline calcium phosphate phases inside the collagen fibril. Because nucleation inhibitors do not need to enter collagen fibrils to induce mineralization, 47 a third theory was recently proposed in which the negatively charged or positively charged polyelectrolytes reside in the extrafibrillar region to establish a balance between electroneutrality and osmotic equilibrium in the vicinity of the collagen fibrils. Establishment of GibbsDonnan equilibrium enables the influx of prenucleation clusters or ACP into the internal milieu of the fibrils to result in intrafibrillar mineralization.…”
mentioning
confidence: 99%
“…Lines above bars indicate p , 0.05. rsfs.royalsocietypublishing.org Interface Focus 6: 20150070 techniques have been employed. These included simply immersing collagen scaffolds in solutions such as SBF or adding proteins, peptides or other chemicals to help control the mineralization process [3,20,[51][52][53][54][55][56][57]. Simple immersion of collagen leads to surface deposition of mineral either on the surface of fibrils, creating extrafibrillar mineral, or on the surface of dense collagen scaffolds.…”
Section: Discussionmentioning
confidence: 99%